IDENTIFIKASI POTENSI EKOWISATA SUMBER AIR PANAS DI KAMPUNG MATATUN SEBAGAI DESTINASI KAMPUNG WISATA DISTRIK KEBAR KABUPATEN TAMBRAUW PROVINSI PAPUA BARAT - Asiar, Barend; Warami, Hugo; Mofu, Suriel S. (Universitas Papua, 2018)
This study aims to describe the potential of ecotourism Hot Springs in Matatun Village as a tourist village destination in Kebar District Tambrauw Regency, West Papua Province. The potential of ecotourism is expected to provide social benefts, economic and income generating for the welfare of Matatun Village community in accelerating the process of regional development or encouraging the growth of new ventures. The method used in this research is descriptive method by applying qualitative and quantitative analysis. The collection of data and information is done through observation and interview to the owner of tourism object, local government and society. Sources of data in this study include primary data sources and secondary data sources. Data collection techniques used in this study consisted of three parts, namely (1) observation techniques, (2) interview techniques, and (3) documentation techniques.The results showed that the potential of ecotourism hot water source in Matatun Village Kebar District Tambraw Regency covers: (a) religious tourism potential, (b) cultural tourism potential, and (c) tourism potential of tirta (water as a source of medicine), and (2) The management of ecotourism of hot springs is a joint responsibility consisting of government, private, organization and non government, and society, while for the knowledge and ability of Matatun Village people in managing tourist area still need to be improved through tourism management training in order to be able to host good in welcoming travelers.